Developing Quantum Learning-Based Junior High School Mathematics Learning Media to Improve Critical Thinking Skills and Self-Efficacy in Eighth Grade Students - Fadhilah, Puji Chairu; Dewi, Izwita; Khairani, Nerli (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
This study aims to develop interactive learning media based on iSpring Suite 11 on number pattern material using the Quantum Learning learning model to improve critical thinking skills and self-efficacy of junior high school students. This type of research is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were eighth grade students at a junior high school in Medan City. The validation results showed that the developed media obtained a very valid category with an average score above 85%. Limited trials showed that this interactive learning media was effective in improving critical thinking skills and self-efficacy of students, with an average N-Gain of critical thinking skills of 0.68 (medium category) and self-efficacy of 0.71 (high category). Thus, interactive learning media based on iSpring Suite 11 is suitable for use as an innovative learning media in mathematics learning based on Quantum Learning, because it is able to improve critical thinking skills and self-efficacy of students